Analysis of the Project-Based Learning Model to Internalize the Value of Gotong Royong in English Learning of Class X OTKP at SMKS Kristen Tomosa 2 - Juni Hati Kristiani Hulu; Kristof Martin E. Telaumbanua; Elwin Piarawan Zebua; Hidayati Daeli (Jurnal Pendidikan dan Sastra Inggris, 2025)
This study aims to analyze the effectiveness of the Project-Based Learning (PBL) model in internalizing the value of gotong royong (mutual cooperation) in English learning among class X OTKP students at SMKS Kristen Tomosa 2. It also explores the experiences, interactions, and perceptions of both students and teachers during the learning process. Using a qualitative approach with descriptive analysis, the study employed instruments such as observation sheets, interviews, and documentation to gather data. The findings reveal that the PBL model significantly enhanced collaboration among students and deepened their understanding of English learning materials. Through project activities, students learned to work together, share responsibilities, and engage in positive interactions, which facilitated the internalization of the gotong royong value. The project activities encouraged teamwork and mutual support, contributing to the development of students' social character. In conclusion, the PBL model proved effective in promoting both academic achievement and the internalization of cultural values such as gotong royong. The study highlights the potential of PBL as a tool for fostering cooperation, improving learning outcomes, and shaping students’ social character in the classroom. Future research could explore its impact on other aspects of character development and academic skills.